INITIAL DESIGN FOR LEARNING THEORY INTRODUCTION TO RIEMANN GEOMETRY THROUGH AN ETHNOMATHEMATICS LEARNING APPROACH - Nugroho, Khathibul Umam Zaid; Widada, Wahyu; Anggoro, Abdurrobbil Falaq Dwi; Anggoro, Shadaqnas Dewarif Tri (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
Riemann Geometry is a difficult elective for students. The ethnomathematics approach is one way to make it easier for students to learn geometry. The aim of this research is to produce a learning theory for Introduction to Riemann Geometry through an ethnomathematics learning approach that is valid. This research method applies a research design. There are three stages, namely Preliminary Research; Prototype, and the last is the Assessment Stage. The results of this research are that the learning and its tools are valid based on validation by seven experts. In conclusion, the initial design of the learning theory for Riemann Geometry is very valid.